Governance and the Peoples Mandate: The Niger Delta Development Commission (NDDC) Revisited, under the Change Agenda - Mukoro, Akpomuvire (International Journal of Public Administration Studies, 2024)
The Niger Delta region of Nigeria has become a paradox of poverty, underdevelopment and neglect in the midst of wealth. The region is endowed with rich deposits of crude oil, but its people are suffering from excruciating poverty, environmental degradation and policy neglect. Through historical survey method, the paper explored the earlier cases of agitation for attention before the attainment of independence, and the empirical cases of the regions concerted approach to cry out because of abandonment, policy inconsistencies and a near neglect of the region. The paper explored the subject in terms of government efforts at obviating their palpable efforts at failure, the irresponsibility of the oil exploring and processing companies and the very hazardous cases of environmental degradation. The paper makes a case for the fact that giving attention to the region must become a mandate for every regime, since it has become a policy trust. It went on to alert the present government that the NDDC has a clear mission for the development of the region. And that their renewed hope agenda does not have to look too far. It went further to aver that adopting the polycentric approach to policy making, stakeholders, governments, the communities and the people in the region would become the better for it.